Coupling of Fused Deposition Modeling and Inkjet Printing to Produce Drug Loaded 3D Printed Tablets - Laura Andrade Junqueira; Atabak Ghanizadeh Tabriz; Francisco José Raposo; Luana Rocha Carobini; Urias Pardócimo Vaz; Marcos Antônio Fernandes Brandão; Dennis Douroumis; Nádia Rezende Barbosa Raposo (MDPI AG, 2022)
In the current study, we have coupled Fused Deposition Modelling (FDM) for the fabrication of plain polyvinyl alcohol (PVA) tablets followed by dispensing of minoxidil ethanolic solutions using inkjet printing. The use of a drop-on-solid printing approach facilitates an accurate and reproducible process while it controls the deposition of the drug amounts. For the purpose of the study, the effect of the solvent was investigated and minoxidil ink solutions of ethanol 70% v/v (P70) or absolute ethanol (P100) were applied on the plain PVA tablets. Physicochemical characterization showed that solvent miscibility with the polymer substrate plays a key role and can lead to the formation of drug crystals on the surface or drug absorption in the polymer matrix. The produced minoxidil tablets showed sustained release profiles or initial bursts strongly affected by the solvent grade used for dispensing the required dose on drug loaded 3D printed tablets. This paradigm demonstrates that the coupling of FDM and inkjet printing technologies could be used for rapid development of personalized dosage forms.